2023
DOI: 10.1002/adfm.202309968
|View full text |Cite
|
Sign up to set email alerts
|

Magneto‐Mechano‐Electric Cascade Stimulation System Accelerates Wound Healing Constructed by Biodegradable Magnetoelectric Nanofibers

Qian Zhang,
Jianhua Zhu,
Hongmei Liu
et al.

Abstract: Reconstructing the intricate biophysical microenvironment to provide multiple biologically beneficial stimulation is deemed a promising therapeutic strategy. However, developing multi‐biophysical stimuli with wireless integration and accurate management remains a formidable challenge. Herein, a novel design of a magneto‐mechano‐electric (MME) cascade stimulation system based on aligned magnetoelectric nanofibrous membranes (PLLA/CFO) is reported. Simply regulating the loading amount of CFO nanoparticles endows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…39,40 Researchers have confirmed that magneto-responsive biocomposites can effectively promote skin wound healing through mechanisms such as modulating cell behavior, magnetic hyperthermia sterilization, and controlled drug release. [41][42][43][44] However, a comprehensive review of magneto-responsive biocomposites as wound dressings has yet to be reported.…”
Section: Lili Haomentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 Researchers have confirmed that magneto-responsive biocomposites can effectively promote skin wound healing through mechanisms such as modulating cell behavior, magnetic hyperthermia sterilization, and controlled drug release. [41][42][43][44] However, a comprehensive review of magneto-responsive biocomposites as wound dressings has yet to be reported.…”
Section: Lili Haomentioning
confidence: 99%
“…This work presents a novel strategy for reconstructing complex biophysical microenvironments remotely. 42 Apart from the magneto-mechano-electric effect, the increase in conductivity due to magnetic anisotropy can also be utilized to enhance intercellular electrical signal transmission. Inspired by the highly ordered hierarchical structure of natural soft tissues, Li et al introduced ordered magneto-electric nanosheets (MPG) into gelatin-oxidized dextran (Gel-ODex) hydrogels, imparting anisotropy to the hydrogel (Fig.…”
Section: Magneto-responsive Biocomposites For Enhancing Electrical Si...mentioning
confidence: 99%
See 1 more Smart Citation
“…19 To date, magneto-electric coupling stimulation has rarely been reported to enhance the endogenous electric field in promoting skin wound healing. 20 This may be attributed to several challenges. On the one hand, traditional magnetic field generation devices rely on large magnets (DC magnetic field) or high-power Helmholtz coils (AC magnetic field), lacking tissue safety and wearability due to high intensity or frequency.…”
Section: Introductionmentioning
confidence: 99%
“…To date, magneto-electric coupling stimulation has rarely been reported to enhance the endogenous electric field in promoting skin wound healing . This may be attributed to several challenges.…”
Section: Introductionmentioning
confidence: 99%